Gawai Raya Kaamatan, 9 June 2023: UiTM Kota Samarahan, Sarawak / Nur Atiqah Husaini ... [et al.] - Husaini, Nur Atiqah; Hamzah, Hanisah Aimi; Abdul Rahman, Abdul Ruqaim Ashraff; Aziz, Syazwani Aqmar (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Gawai Raya Kamamatan is a unique event for AZV members, celebarting Gawai, Hari Raya Aidilfitri and Pesta Kaamatan. For this year each studio competied in an Unduk Ngadau Fashion Show Competition which is a traditiona; beauty competition from Sabah. In the morning each studio was given time to design their respective Unduk Ngadau attire. The fashion show was to be judged by lecturers during ramah tamah event located at Blok G, UiTM Sarawak in the afternoon. While feasting, AZV members were presented with variety of raya song sang by the AZV Buskers team lead by Abang Akmal of Neo Studio. After that the fashion show began with Arctix studio as the opener followed by Neo studio and finally Classix studio. The Unduk Ngadau competition was won by Classix studio with Abdul Ruqaim Ashraff and Nur Ain Azreena as the model representative. Followed by second place, Neo studio and third place Arctix studio. This Unduk Ngadau competition showcased every studio’s teamwork. The program hoped to enhanced students’ creativity outside of architecture scope.